2014
DOI: 10.1007/s10551-014-2249-x
|View full text |Cite
|
Sign up to set email alerts
|

Validation of a Digital Work Simulation to Assess Machiavellianism and Compliant Behavior

Abstract: This paper describes a new and innovative measure that is developed to predict workplace deviance through the measurement of Machiavellianism and Compliant Behavior. Two field studies were conducted to study the validity of the digital work simulation. In Study 1, (N = 113) support was found for the construct validity of the simulation. The constructs as measured with the simulation correlated significantly with self-reported measures of the constructs and were related to personality and selfesteem. Study 2 (N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 88 publications
0
5
0
Order By: Relevance
“…Finally, we did not control for social desirability in our study. We are aware of only one study that has included measures of social desirability with the Dahling et al (2009) scale (i.e., Dubbelt et al, 2015) and they did find a weak, negative correlation. We cannot rule out the possibility that leaders may have been concerned with social desirability when answering the Machiavellianism scale.…”
Section: Discussionmentioning
confidence: 96%
“…Finally, we did not control for social desirability in our study. We are aware of only one study that has included measures of social desirability with the Dahling et al (2009) scale (i.e., Dubbelt et al, 2015) and they did find a weak, negative correlation. We cannot rule out the possibility that leaders may have been concerned with social desirability when answering the Machiavellianism scale.…”
Section: Discussionmentioning
confidence: 96%
“…In a SJT, participants are confronted with a description of a particular situation, and participants choose one out of several response options. The contents of these SJTs can be presented in a text-based format (e.g., Oostrom et al, 2019 ), a video-based format (e.g., Dubbelt et al, 2015 ), or in a gamified format (e.g., Georgiou et al, 2019 ). To illustrate these studies’ findings, McCord et al (2019) found convergent validity between a gamified assessment of the FFM personality traits and several self-reported FFM personality traits.…”
Section: Prior Research On Assessment Games and Gamified Assessments ...mentioning
confidence: 99%
“…Even in those very limited relevant literature, scholars hold completely opposite opinions. Some regard deferential behaviour as the representation of a cooperative group status process (Driskell and Salas, 1991), while some view it as a workplace deviance (Dubbelt et al , 2015), related to behaving unethically (Wahn, 2003) and having illegal intentions (Smith et al , 2007).…”
Section: Introductionmentioning
confidence: 99%